Policy implementation and coordination capacity: a case study of the state s capacity to implement the National Integrated Early Childhood Development policy in a district in the Eastern Cape, South Africa - Parenzee, Penelope (Graduate School of Development Policy and Practice, 2025)
Early childhood Development (ECD) refers to the suite of interventions – provided to a child from conception until the transition into school, which nurtures and enables the child to thrive and reach their full potential. Of the policy responses directed at addressing inequality, ECD is identified as pivotal in increasing equality in a society and disrupting cycles of poverty across generations (Paananen et al., 2018; Irwin et al., 2007). In the South African context, where inequality and poverty persisted even with the transition to democracy, the prominence of ECD has evolved, culminating in the establishment of a National Integrated ECD Policy (2015). Despite the policy, the provision of integrated, quality ECD services for all children is yet to be realised. Across the country, varying degrees of implementation failures prevail, with devastating consequences for those residing within the poorest areas of the country. The coronavirus 2019 (COVID-19) crisis compounded the urgency to address the ECD policy implementation challenges, with research illustrating how the failure of government to coordinate the implementation of ECD has brought the sector to the brink of collapse (Wills et al., 2020). The emphasis on coordination structures, that are envisaged to oversee streamlined technical solutions, continues to dominate, shaping and re-shaping the implementation landscape. This research study set out to understand the state's capacity to coordinate the implementation of the NIECD policy. Through the use of case study methodology, the research delves into the implementation of ECD in a district in the Eastern Cape province. Howlett's (2018) multiple streams/critical junctures policy framework was applied to make sense of the implementation realities that plague the ECD sector. To deepen the understanding of coordination capacity – aspirational and existing - Wu et al's (2015) policy capacity matrix provided a complementary analytical framework. Based on the findings from this research study, there is a need to reconsider the focus on coordination structures for the ECD sector to challenge the perception that coordination constitutes structures as a way of dealing with the challenges of ECD policy implementation. Instead, a shift towards far more inclusive local level engagement may contribute to a renewed consideration of coordination as that of working within the complexities of diverse contexts. The focus of this research study is opportune, as it can contribute to the current debates on coordination capacity for the implementation of ECD services in South Africa.